Inhibitory activity of postbiotic produced by strains of Lactobacillus plantarum using reconstituted media supplemented with inulin - Kareem, Karwan Yassen; Foo, Hooi Ling; Loh, Teck Chwen; Ooi, May Foong; Samsudin, Anjas Asmara @ Ab Hadi (BioMed Central, 2014)
Background: The present study aimed to determine the inhibitory activity of postbiotic produced by L. plantarum using reconstituted media supplemented with different levels of inulin and to select the best combination based on the modified inhibitory activity (MAU/mL) against pathogens. Methods: Postbiotics were produced by 6 strains of L. plantarum (RG11, RG14, RI11, UL4, TL1 and RS5) using reconstituted media supplemented with different levels of Inulin (0, 0.2, 0.4, 0.6, 0.8, and 1.0) yielding 36 combinations. Results: The combination of postbiotic and inulin had higher inhibitory activity than postbiotic alone against all indicator organisms except Pediococcus acidilactici, and E. coli. The RI11 + 0.8% Inulin, RG14 + 0.8% Inulin and RG14 + 0% Inulin had significantly (p < 0.05) higher MAU/mL against P. acidilactici than other treatments. The RI11 + 0.8% Inulin and RG14 + 0.4% Inulin had a significantly (p < 0.05) higher MAU/mL against VRE. The MAU/mL against L. monocytogenes was greater in RI11 + 1.0% Inulin, RI11 + 0.6% Inulin and RI11 + 0.8% Inulin. The combinations of RS5 + 1.0% Inulin, RS5 + 0.8% Inulin and RS5 + 0.6% Inulin had greater MAU/mL against S. enterica; whereas in E. coli, the inhibitory activity had higher activity that can only be found in RS5 + 0.8% Inulin. Conclusion: Combination of postbiotics and inulin which had higher optical density tends to have lower pH which corresponds to increased inhibitory activity against indicator organisms. The results of this study show that postbiotics and inulin supplementation enable to inhibit proliferation of pathogenic bacteria.